DYNAMICS OF ADAT LAW COMMUNITY RECOGNITION: STRUGGLE TO STRENGTHEN LEGAL CAPACITY - Sartika Intaning Pradhani (Fakultas Hukum Universitas Gadjah Mada, 2019)
AbstractThe existence of adat law community has been recognized since Dutch Colonial Era until today. State recognitions towards adat law community are dynamics. This paper is written based on legal normative research to describe dynamics of adat law community recognition. In the early of Indonesia independent, adat law community was considered as foundation of Indonesia nation state establishment. Since 1957 and during New Order era, there was systematic effort to abolish adat law communities because adat law was perceived as symbol of backwardness. After the amendment of the Constitution, adat law community and their traditional rights are recognized by law and enforced through court decision. Adat law community can determine their type of recognition to strengthen their legal capacity to manage Adat Forest; to organize Adat Village; or to hold communal land rights. IntisariEksistensi masyarakat hukum adat telah diakui sejak zaman Pemerintahan Kolonial Belanda hingga hari ini. Pengakuan negara terhadap masyarakat hukum adat bersifat dinamis. Tulisan ini ditulis berdasarkan penelitian hukum normatif untuk mendeskripsikan dinamika pengakuan masyarakat hukum adat. Pada awal kemerdekaan Indonesia, masyarakat hukum adat merupakan dasar terbentuknya negara bangsa Indonesia. Sejak tahun 1957 dan selama periode Order Baru, ada upaya sistematis untuk menghapuskan masyarakat hukum adat karena hukum adat dianggap sebagai simbol keterbelakangan. Pasca amandemen konstitusi, masyarakat hukum adat dan hak tradisionalnya diakui melalui hukum dan ditegakkan oleh pengadilan. Masyarakat hukum adat dapat menentukan jenis pengakuan yang dapat menguatkan kapasitas hukum mereka dalam mengelola hutan adat; mengorganisasi Desa Adat; atau dalam menyandang hak komunal atas tanah. AbstractAbstractThe existence of adat law community has been recognized since Dutch Colonial Era until today. State recognitions towards adat law community are dynamics. This paper is written based on legal normative research to describe dynamics of adat law community recognition. In the early of Indonesia independent, adat law community was considered as foundation of Indonesia nation state establishment. Since 1957 and during New Order era, there was systematic effort to abolish adat lawcommunities because adat law was perceived as symbol of backwardness. After the amendment of the Constitution, adat law community and their traditional rights are recognized by law and enforced through court decision. Adat law community can determine their type of recognition to strengthen their legal capacity to manage Adat Forest; to organize Adat Village; or to hold communal land rights.